Secular Martyrdom in Britain and Ireland
XVII, 346 p. 7 illus.
Keywords: This edited collection examines the concept and nature of the ‘people’s martyrology’, raising issues of class, community, religion and authority. It examines modern martyrdom through studies of Peterloo; Tolpuddle; Featherstone; Tonypandy; Emily Davison, fatally injured by the King’s horse on Derby Day, 1913; the 1916 Easter Rising; Jarrow, ‘the town that was murdered, and martyred in the 1930s’; David Oluwale, a Nigerian killed in Leeds in 1965; and Bobby Sands, the IRA hunger striker who died in 1981. It engages with the burgeoning historiography of memory to try to understand why some events, such as Peterloo, Tonypandy and the Easter Rising, have become household names whilst others, most notably Featherstone and Oluwale, are barely known. It will appeal to those interested in British and Irish labour history, as well as the study of memory and memorialization.